2018
DOI: 10.1038/s41419-018-0355-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation induced by lipopolysaccharide aggravates inherited retinal dystrophy

Abstract: Retinal neurodegenerative diseases involve a scenario of inflammation and cell death that leads to morphological alterations and visual impairment. Non-ocular inflammatory processes could affect neurodegenerative retinal disorders and their progression, at least in part by activating microglial cells and releasing pro-inflammatory cytokines. Our purpose was to study the consequences of a systemic inflammatory process in the progression of retinal degeneration in P23H rats, a retinitis pigmentosa (RP) model. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 83 publications
13
46
0
Order By: Relevance
“…5,10,[57][58][59][60][61][62] In all retinal degenerative diseases, photoreceptor degeneration is accompanied by the proliferation and activation of resident microglia and by the recruitment of immune cells as monocytes and macrophages, which contribute to the inflammatory state of the tissue. 10,31,33 Accordingly, our results show an increase in the immune cells implicated in the inflammatory process in rd10 mice. However, rd10 mice raised in different light conditions showed few differences in the immune-related cells populations, probably due to the advanced state of the degenerative process at the endpoint of the study (P30).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…5,10,[57][58][59][60][61][62] In all retinal degenerative diseases, photoreceptor degeneration is accompanied by the proliferation and activation of resident microglia and by the recruitment of immune cells as monocytes and macrophages, which contribute to the inflammatory state of the tissue. 10,31,33 Accordingly, our results show an increase in the immune cells implicated in the inflammatory process in rd10 mice. However, rd10 mice raised in different light conditions showed few differences in the immune-related cells populations, probably due to the advanced state of the degenerative process at the endpoint of the study (P30).…”
Section: Discussionsupporting
confidence: 68%
“…Cornea, lens, and vitreous body were removed, and the eyecups were prepared for cross-sectional cryosections as previously described by our group. [30][31][32] Sections 16-μm thick were obtained and stored at -20°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The gradual photoreceptor loss characteristic of P23H line-3 rats provides an experimental model closer to RP patients than other animal models (Machida et al, 2000 ; Cuenca et al, 2004 ). This vascular study completes a series of studies conducted by our research group analyzing the morphological and functional changes occurring during the degenerative process of homozygous P23H line-3 rats, including changes in astrocytes, microglia and Müller cells (Esquiva et al, 2017 ; Cuenca et al, 2014 ; Fernández-Sánchez et al, 2015a ; Lax et al, 2016 ; Noailles et al, 2016 , 2018 ). We have chosen homozygous vs. heterozygous P23H line-3 rats because our previous results have demonstrated that degeneration in the homozygous model is more aggressive but slow enough to properly assess neuroprotective effects of various compounds (Fernández-Sánchez et al, 2011 , 2012a , b , 2015b , 2017 ; Lax et al, 2011 ; Noailles et al, 2014 ).…”
Section: Discussionsupporting
confidence: 55%
“…www.nature.com/scientificreports/ their microglia display smaller round bodies with few dendrites 30,31 . In the more slowly progressive P23H RHO rat and P23H Rho mouse, microglia retract their dendrites yet maintain an intermediate ramified phenotype 27,32,33 . Thus morphological activation of microglia towards a large, ameboid phenotype likely occurs in proportion to the size of the phagocytic bolus introduced by retinal degeneration, and may have important implications for cell signaling, such as the production of IL-1β 34 .…”
Section: Discussionmentioning
confidence: 99%